Determining the Basic Variables for Diagnosis of Patients With Thyroid Gland By Using S/N Ratio Methods. - Rashid, Kawa M. Jamal (Sulaimani Journal for Pure and Applied Sciences, 2015)
There are many situations in which the simultaneous monitoring or control of two or more related quality characteristics is necessary. Multivariate analysis utilize the additional information due to the relationships among the variables and these concepts may be used to develop more efficient control charts than the simultaneous operation of several university control charts. The most popular multivariate statistical process control SPC are the Hotelling's T2 chart. In this paper the S/N ratio is analyzed and response effect level are calculated with optimizing the response effect level And to explain which of variable is important and necessary to test the chemical analysis in Thyroid gland.
Keywords: HotellingT2 chart Signaltonoise ratio SN